The Implementation of Role Play in Teaching Future Tense - Haris Dibdyaningsih; Hendra Sudarso (Journal of English Language Teaching and Islamic Integration, 2020)
Future tense is one of important part of daily communication, students need to know the future tense well otherwise they get misunderstanding of speakers’ purpose. Some students get confused and have difficulties in defining part of a sentence. So, it is important for them to know the tense well. Moreover, the purpose of this study was to know about the improvement of student’s future tense understanding after they were taught by using role play. This research used a quantitative approach and it was conducted to 15 students in class 2019 semester 1. The data of the research collected using a paper based test of future tense. The result showed that there was significant improvement in students’ future tense understanding after they got role play. It could be proven from the improvement of students’ average score from the pretest and post-test, which was 59 to 82,6, hypothesis test showed that t-table is 2,145 and the t-value is 14,992. In conclusion, role play technique can improve students’ future tense understanding